Prekletstvo številke 45 - Konovšek, Tjaša (Prispevki za novejšo zgodovino, 2020)
Constituting the Slovene parliament and government in the 90s was deeply marked by the transition and polarization of Slovene political space. This paper spatially and temporarily frames the historical event and then focuses on a case study of parliamentary and government constitution. It analyses the formal perspective of the process and informal arrangements that crucially shaped the constituting process. This kind of research reveals the depth of parliamentary parties' polarization. The political discourse was woven around for identifications that manifested the polarization. Left-leaning parties, Liberal democratic party (Liberalna demokracija Slovenije) being the most dominant, understood themselves as pro-Europe parties that will bring West-type normality, while right-leaning Slovene people's party (Slovenska ljudska stranka), Slovene Christian democrats (Slovenski krščanski demokrati), and Slovene democratic party (Slovenska demokratska stranka) named themselves spring parties. The first group understood the opposing parties as hindrances to the normalization process, while right-leaning parties feared continuity with socialism and marked the left-leaning parties as old forces. The repeating defeat of right-wing parties (with a few months exceptions in 2000) reinforced their negative discourse, which fully emerged after the end of the transition.
Keywords: državni zbor; parlamentarizem; politična zgodovina; politika; Slovenija; tranzicija; vlada; zgodovina